ACTIVITY BASED COSTING SYSTEM : MODEL PENELUSURAN BIAYA OVERHEAD YANG AKURAT PADA UMKM SILK HOUSE SABBENA SOPPENG - Syamsu Alam (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2020)
This study aims to trace the absorption of overhead costs in the production process at Sabbena Soppeng's silk house, to identify appropriate cost drivers in allocating overhead costs to products that are accurate and do not occur distortion. This research uses descriptive method. Collecting data through interviews, observation, documentation. The analysis was carried out by applying a two-stage activity-based costing model. First, trace overhad costs to the “cost pool”. Second, trace the overhead costs to the product using multiple cost drivers. The results showed: a) the product category " Kain Sutera" shows a smaller difference of Rp. 3,253.62; b) product category "Sarung sutra ST-0 Standar" shows a bigger difference of Rp 10,997.4; c) product category "Sarung sutera ST-1 Standar" shows a bigger difference of Rp 22,420.49; d) product category "Sarung sutera ST- Sedang" shows a bigger difference of Rp. 28,352.51; e) product category “Sarung Sutera ST-ASL” shows a bigger difference of Rp. 278,342.75. The difference is due to the fact that the traditional overhead system does not use several cost drivers. Meanwhile, the ABC system uses a multi cost driver in charging BOP. So that with the ABC System it is considered that the BOP allocation is more accurate. Keywords : Activity Based Costing, Cost of Production.